2019
DOI: 10.3390/pr7050258
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of CO2 Solubility in Ionic Liquids Based on Multi-Model Fusion Method

Abstract: Reducing the emissions of greenhouse gas is a worldwide problem that needs to be solved urgently for sustainable development in the future. The solubility of CO2 in ionic liquids is one of the important basic data for capturing CO2. Considering the disadvantages of experimental measurements, e.g., time-consuming and expensive, the complex parameters of mechanism modeling and the poor stability of single data-driven modeling, a multi-model fusion modeling method is proposed in order to predict the solubility of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The results showed that COSMO-RS can be a useful and practical predictive tool. The employment of intelligent methods to predict the solubility of various gases such as N 2 O 26 , SO 2 27 , 28 , H 2 S 24 , 29 , and CO 2 30 in ILs has received much attention in the last decade, and the results confirm the reliability of these methods. Using the thermodynamic properties of ILs and 728 experimental data, Baghban et al 31 developed a multi-layer perceptron (MLP) model and an adaptive neuro-fuzzy interference system (ANFIS) to predict the solubility of CO 2 in ILs and then compared the results with the equations of state.…”
Section: Introductionmentioning
confidence: 89%
“…The results showed that COSMO-RS can be a useful and practical predictive tool. The employment of intelligent methods to predict the solubility of various gases such as N 2 O 26 , SO 2 27 , 28 , H 2 S 24 , 29 , and CO 2 30 in ILs has received much attention in the last decade, and the results confirm the reliability of these methods. Using the thermodynamic properties of ILs and 728 experimental data, Baghban et al 31 developed a multi-layer perceptron (MLP) model and an adaptive neuro-fuzzy interference system (ANFIS) to predict the solubility of CO 2 in ILs and then compared the results with the equations of state.…”
Section: Introductionmentioning
confidence: 89%
“…An example of the application of machine learning for studying gas hydrates can be found in the work done by Xia et al [216]. They incorporated a fusion modeling method that could be used to predict CO 2 solubility in hydrates as related to nine ionic liquids.…”
Section: Machine Learningmentioning
confidence: 99%
“…Using the information entropy method to determine the weight coefficient of each sub-model can effectively reduce the impact of the weak sub-model on the model performance [29]. In this paper, the information entropy method is used to obtain the weight coefficient of the optimal sub-model [11].…”
Section: Sub-model Ensemblementioning
confidence: 99%
“…Although the mechanism modeling method has the advantage of strong model interpretability, thermodynamic model is relatively complex and requires complicated mathematical operations [10]. Considering the complex parameters of mechanism model, a multi-model fusion method was proposed to predict the solubility of CO 2 in ionic liquids [11].…”
Section: Introductionmentioning
confidence: 99%